Effects of the maize-derived protein zein, and the milk proteins casein, whey, and α-lactalbumin, on subjective measures of satiety and food intake in normal-weight young men. (1st January 2023) - Chungchunlam, Sylvia M.S.; Montoya, Carlos A.; Stroebinger, Natascha; Moughan, Paul J.
Abstract: Protein is considered to be the most satiating food macronutrient and the satiating effect may be dependent on the source of the protein. The maize-derived protein zein and milk protein casein have been shown previously to lower stomach emptying rate more than dairy whey protein, but the effect of zein on satiety has not been evaluated. The objective was to compare the satiating effects of zein and casein, with whey protein and its protein component α-lactalbumin. The study was a randomised crossover design with thirteen normal-weight men (mean age 27.8 years and mean BMI 24.4 kg/m 2 ) consuming isoenergetic (∼4000 kJ, ∼990 kcal) preload mixed meals enriched with Zein, Casein, whey protein isolate (Whey), α-lactalbumin (ALac), or maltodextrin carbohydrate (Carb). Consumption of an ad libitum standardised test meal of chicken fried rice and water provided 360 min following ingestion of the preload meal was measured, and subjective feelings of appetite (hunger, fullness, desire to eat, and prospective food consumption) were assessed using 100-mm visual analogue scales (VAS). There were no differences among the five preload mixed meals in the amount of chicken fried rice consumed at the ad libitum test meal (mean ± sem: 531.6 ± 35.0 g, p  = 0.47) or total (preload + test meal) energy intakes (mean ± sem: 5780.5 ± 146.0 kJ, p  = 0.29). The subjective VAS appetite ratings and total area under the curve responses for hunger, fullness, desire to eat, and prospective food consumption, were not different following consumption of all five preload mixed meals ( p  > 0.05). The findings indicate that the effects of zein and casein on satiety were not different from the satiating effects of whey protein and α-lactalbumin.